Deleterious ZNRF3 germline variants cause neurodevelopmental disorders with mirror brain phenotypes via domain-specific effects on Wnt/β-catenin signaling - Boonsawat, Paranchai; Asadollahi, Reza; Niedrist, Dunja; Steindl, Katharina; Begemann, Anaïs; Joset, Pascal; Bhoj, Elizabeth J.; Li, Dong; Zackai, Elaine; Vetro, Annalisa; Barba, Carmen; Guerrini, Renzo; et al. (American Journal of Human Genetics, 2024)
Zinc and RING finger 3 (ZNRF3) is a negative-feedback regulator of Wnt/β-catenin signaling, which plays an important role in human brain development. Although somatically frequently mutated in cancer, germline variants in ZNRF3 have not been established as causative for neurodevelopmental disorders (NDDs). We identified 12 individuals with ZNRF3 variants and various phenotypes via GeneMatcher/Decipher and evaluated genotype-phenotype correlation. We performed structural modeling and representative deleterious and control variants were assessed using in vitro transcriptional reporter assays with and without Wnt-ligand Wnt3a and/or Wnt-potentiator R-spondin (RSPO). Eight individuals harbored de novo missense variants and presented with NDD. We found missense variants associated with macrocephalic NDD to cluster in the RING ligase domain. Structural modeling predicted disruption of the ubiquitin ligase function likely compromising Wnt receptor turnover. Accordingly, the functional assays showed enhanced Wnt/β-catenin signaling for these variants in a dominant negative manner. Contrarily, an individual with microcephalic NDD harbored a missense variant in the RSPO-binding domain predicted to disrupt binding affinity to RSPO and showed attenuated Wnt/β-catenin signaling in the same assays. Additionally, four individuals harbored de novo truncating or de novo or inherited large in-frame deletion variants with non-NDD phenotypes, including heart, adrenal, or nephrotic problems. In contrast to NDD-associated missense variants, the effects on Wnt/β-catenin signaling were comparable between the truncating variant and the empty vector and between benign variants and the wild type. In summary, we provide evidence for mirror brain size phenotypes caused by distinct pathomechanisms in Wnt/β-catenin signaling through protein domain-specific deleterious ZNRF3 germline missense variants.
CRIS-Team Scopus Importer:2024-09-13
Keywords: adrenal insufficiency; congenital heart defects; dominant negative; haploinsufficiency; macrocephaly; microcephaly; mirror phenotype; tumor suppressor gene; Wnt signaling; ZNRF3